Influence of Specimen Size on Autogenous Volume Deformation of Long-Aged MgO-Admixed Concrete - Chen, Changli; Chen, Rongfei; Zhao, Zhenhua; Li, Weiwei; Yan, Shaolian; Du, Xiangqin; Yang, Huashan (Frontiers in Materials, 2021)
The transformation law of autogenous volume deformation of MgO-admixed concrete with specimen size is revealed through continuous observation on standard size (Φ200 mm × 500 mm), medium size (Φ250 mm × 500 mm) and large size specimens (Φ250 mm × 600 mm) over 6 years, and observing the pore parameters of concrete core samples by drilling from autogenous volume deformation specimens in the 1st, 3rd and 6th year of age. The results show that the autogenous volume deformation of MgO-admixed concrete rises with the rising of MgO content or age. After the ages of 360 days, the expansion rate of the concrete specimen decreases. When the size of the specimen changes, the autogenous volume deformation of MgO-admixed concrete decreases with the increase of specimen size. After about the ages of 2 years, the autogenous volume expansion of the specimen tends to be stable, and with the same MgO content, the expansion of the standard specimen is about 5 × 10-6~ 10 × 10-6 larger than that of the medium specimen, and about 10 × 10-6~ 20 × 10-6 larger than that of the large specimen.